Adressing congestion on a rail network with a decentralised incentive scheme - Kveiborg, Ole (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
The paper suggests using a decentralised mechanism design incentive scheme as a solution to the delays caused in a rail network due to insufficient quality by the service providers. Some issues concerning the practical implementation of such a system in a real situation are discussed.